Public Speaking Ability Analysis of Traffic Police Officer In Socialization Traffic Rule in resort Ungaran , Kabupaten Semarang - Phopy Harjanti Bulandari; Hedi Pudjo Santosa; Much Yulianto; Agus Naryoso (Interaksi Online, 2015)
This study was conducted to see how the ability Police Officer in Public Speaking for socialization orderly traffic in Kab.Semarang districtThe purpose of this study was to determine the forms of public speaking activities undertaken within the framework of the Indonesian National Police Traffic orderly dissemination and to evaluate the ability of the Public Speaking Police Officer in the socialization of traffic rules in Police in Ungaran. Kab. Semarang 2014 .The results showed that the police officers while providing socialization begins with wearing uniform look neat and fresh and fresh face. Mastery of traffic police officers in socialization orderly traffic in the jurisdiction of police station Ungaran . The use of verbal language using words that are easily understood , a series of sentences neatly arranged, delivery of messages using long sentences and material power point of interest . Confidence traffic police officer noticed aspect of " pause " and this is a good effort made by the traffic police officer in the socialization orderly traffic in the jurisdiction of police station Ungaran . Interaction and communication officers are able to blend , capable of interacting , able to provide feedback and conduct a question and answer with the audience .